Apakah perceived social support memoderasi peran loneliness terhadap quarter-life crisis pada fresh graduate? - Raviqa Mawaddah; Aflah Zakinov Irta (SUKMA : Jurnal Penelitian Psikologi, 2026)
Abstract   This study aims to examine the effect of loneliness on the quarter-life crisis and the role of perceived social support as a moderator among recent graduates. The study employs a quantitative approach with a correlational design. The sample consisted of 290 recent graduates aged 21–25 years, selected using incidental sampling. Data were collected using the UCLA Loneliness Scale Version 3, the Quarter-Life Crisis Scale, and the Multidimensional Scale of Perceived social support (MSPSS), and then analyzed using SEM-PLS. The results indicate that loneliness has a positive and significant effect on the quarter-life crisis. However, perceived social support does not have a significant effect on the quarter-life crisis and was not found to moderate the relationship between loneliness and the quarter-life crisis. These findings suggest that loneliness is a key factor in the emergence of quarter-life crisis experiences among fresh graduates. Therefore, strengthening psychological resources can help fresh graduates cope with various challenges during the transition from the academic world to the workforce.   Penelitian ini bertujuan untuk menguji hubungan loneliness terhadap quarter-life crisis serta peran perceived social support sebagai variabel moderator pada fresh graduate. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 290 fresh graduate berusia 21–25 tahun yang dipilih menggunakan teknik incidental sampling. Data dikumpulkan menggunakan UCLA Loneliness Scale Version 3, skala Quarter-Life Crisis, dan Multidimensional Scale of Perceived social support (MSPSS), kemudian dianalisis menggunakan SEM-PLS. Hasil penelitian menunjukkan bahwa loneliness berpengaruh positif dan signifikan terhadap quarter-life crisis. Namun, perceived social support tidak berpengaruh signifikan terhadap quarter-life crisis dan tidak terbukti memoderasi hubungan antara loneliness dan quarter-life crisis. Temuan ini menunjukkan bahwa loneliness merupakan faktor yang berperan penting dalam munculnya pengalaman quarter-life crisis pada fresh graduate. Oleh karena itu, penguatan sumber daya psikologis dapat membantu fresh graduate menghadapi berbagai tantangan pada masa transisi dari dunia pendidikan menuju dunia kerja.